FRONTPAGE PROJECT - Pericleous, Vicky; Maragaki, Eva; Nottas, Marios; Sysalova, Julia (My University, 2024)
FRONTPAGE PROJECT - Exhibition | Symposium | Workshop, Department of Fine Arts, School of Fine and Applied Arts, CUT - Cyprus University of Technology, Limassol Municipal University Library, November 20 – 29, 2024 Group exhibition | symposium | workshop centered on the themes of "front page" and "headline news" in print and digital media. Participants include artists and cultural producers from the visual arts, from academic fields, and the media. The Department of Fine Arts at the School of Fine and Applied Arts of Cyprus University of Technology (CUT) develops and organises the second part of the international investigative project FRONTPAGE in collaboration with the European Communication Institute (ECI), in partnership with the Athenian Macedonian News Agency (AMNA) and the open visual arts group AxionArt and the collaboration of the Video Art Festival Miden (Mηδέν). It is supported by various academic institutions, including Donau-Universität Krems (DUK). In Cyprus, the research project is curated and organised by assistant professor and visual artist Vicky Pericleous and [Ρε:Re] Speculative Fine Art Practices Lab (CUT), which she develops and coordinates, visual artist Andreas Savva (special teaching staff), and curatorial assistant, Rebecca Taki, student of the MA History and Theory of Art, (CUT), with the support and involvement of the Department of Fine Arts (CUT). The FRONTPAGE project will unfold through a public symposium featuring esteemed academic speakers addressing topics relevant to the project, alongside the international FRONTPAGE exhibition at Limassol Municipal University Library, and a visual art workshop that engages academics from various fields and students from the Department of Fine Arts at CUT. The outcomes of the workshop will be presented in 2025 in Athens in an expanded exhibition featuring student work from the Athens and Thessaloniki Schools of Fine Arts, the University of West Attica (ΠΑ.Δ.Α.), the Department of Digital and Performing Arts of the University of Peloponnese, the Ionian University, as well as contributions from established artists. *International Art Exhibition: November 20 – 29, 2024, Limassol Municipal University Library. Exhibition Opening: Wednesday, November 20, 6:00 PM – 8:30 PM. Exhibition Hours: Monday - Friday: 8:00 AM - 2:30 PM. Contact: 25-362155, 25-002211, Municipal Building, 269 Karaiskaki & Agiou Andrea, 3035 Limassol. Invited Artists | Cultural Producers: George Gyzis (Greece), Eleni Zouni (Greece), Kyriakos Kallis (Cyprus), Yiannis Christidis, (Cyprus), Makis Faros (Greece), Nikos Kouroussis (Cyprus), Kyriakos Kousoulides (Cyprus), Theopisti Stylianou-Lambert and Nicolas Lambouris (Cyprus), Eva Maragaki (Greece), Demetris Neokleous (Cyprus), Omiros Panayides(Cyprus), Aspasia Papadima (Cyprus), Vicky Pericleous (Cyprus), Nikos Podias (Greece), Artemis Potamianou (Greece), Andreas Savva (Cyprus), Efi Savvides (Cyprus), Anneta Spanoudaki (Greece), Marios Spiliopoulos (Greece), Nicos Synnos (Cyprus), Panos Tsagaris (Greece), Kostas Tsolis (Greece), Hourig Torossian (Cyprus), Dimitra Chanioti (Greece), Savvas Christodoulides (Cyprus), Yioula Hatzigeorgiou (Cyprus), Horst Weierstall (Cyprus/Germany). Video Art | Festival Miden: Sandra Araujo (Portugal), Katina Bitsicas (USA), Pamela Falkenberg & Jack Cochran (Outlier Moving Pictures) (USA), Rodrigo Amarante Guerreiro Gomes (Portugal), Niki Kapokaki (Greece), Kristýna Kopřivová (Czech Republic),Smaragda Nitsopoulou (Greece), Gioula Papadopoulou (Greece), Bruno Pavić (Croatia), John O’Hare & Tom Phipps (UK), Guli Silberstein (UK), Kuesti Fraun & Andreas Uehlein (performer) (Germany), Martha Tsiara (Greece), Chris Tigra (Brazil), Jack Williams (Poland), Jody Zellen (USA). *With the Participation of the Program MIXANITOUXRONOU (ΜΗΧΑΝΗ ΤΟΥ ΧΡΟΝΟΥ) (TIME MACHINE), produced by ERT, (broadcast/show based on research, documentaries, tributes, and interviews referencing history, culture, and society) | Creators: Journalists Christos Vassilopoulos and Dimitris Petropoulos (Greece) and video: Panagiotis Parnassas *At the exhibition's opening, the documentary of the tv show MIXANITOUXRONOU, produced by ERT, 2023, will be presented, with the FRONTPAGE project as its subject. A guided tour by the project curatorial team will follow. The in situ performance "CRYME," 2024, a live dialogue of sound and image, between Giannis Christidis and Kyriakos Kousoulidis will be presented at 19:45. *The new site-specific sculptural installation Odyssey II, 2024, by Nikos Kouroussis is presented at the garden of the library, as an expansion of Kouroussis’ work, Odyssey, presented in the Venice Biennale, 1990. *In the context of the FRONTPAGE project and in collaboration with the Erasmus Office of the Cyprus University of Technology, Kristýna Kopřivová (Czech Republic), a filmmaker and researcher, presents Before the Storm, 2024, a short documentary video art. The screening will be followed by a talk from the author. Wednesday 27 November, 18:00, Tseriotis Building.
FRONTPAGE PROJECT - Exhibition, Symposium, Workshop
Keywords: Arts; Exhibitions/Publications; Catalogue; Digital; Frontpage; News; Communication; Social-political Constructs & Representations in the Arts & Communication; Politics; Cultural relationship of word and image